Acquired Glanzmann thrombasthenia: From antibodies to anti-platelet drugs. (July 2019) - Nurden, Alan T.
Abstract: In contrast to the inherited platelet disorder given by mutations in the ITGA2B and ITGB3 genes, mucocutaneous bleeding from a spontaneous inhibition of normally expressed αIIbβ3 characterizes acquired Glanzmann thrombasthenia (GT). Classically, it is associated with autoantibodies or paraproteins that block platelet aggregation without causing a fall in platelet count. However, inhibitory antibodies to αIIbβ3 are widely associated with primary immune thrombocytopenia (ITP), occur in secondary ITP associated with leukemia and related disorders, solid cancers and myeloma, other autoimmune diseases, following organ transplantation while cytoplasmic dysregulation of αIIbβ3 function features in myeloproliferative and myelodysplastic syndromes. Antibodies to αIIbβ3 occur during viral and bacterial infections, while drug-dependent antibodies reacting with αIIbβ3 are a special case. Direct induction of acquired GT is a feature of therapies that block platelets in coronary artery disease. This review looks at these conditions, emphasizing molecular mechanisms, therapy, patient management and future directions for research.